Perspective Directions of Improving Energy Efficiency on the Meso and Micro Levels of the Economy - MALYSHEVA, Tatiana V.; SHINKEVICH, Alexey I.; OSTANINA, Sofia Sh.; VODOLAZHSKAYA, Ekaterina L.; MOISEYEV, Vadim O. (Journal of Advanced Research in Law and Economics; Vol 7 No 1 (2016): JARLE Volume VII, Issue 1(15), Spring 2016, 2016)
The relevance of the research is reasoned by the study of the important issue on energy efficiency’s increasing of the economy at mezzo and micro levels. In conditions of the innovation economy’s development energy saving becomes a major factor in improving of economic efficiency and economic security of industrial plants and complexes. The purpose of the paper is to develop a methodology for assessing of the energy intensity of the economy, depending on industrial structural changes, the scale of production and value-added components. As the research’s leading method of the average value changes of energy consumption is proposed a method for constructing of a system of three interrelated indices combining different parameters of the structural elements of economic systems. The basic form for monitoring of energy saving processes in the real sector is an indicative method to ensure timely assessment of capacity at the mezzo and micro levels of the economy and increasing the validity of management decisions in this area. The scientific novelty of the research is to develop methods to assess the energy intensity of the economy depending on external and internal factors. In the paper the research mechanism is proposed to study the effect of structural shifts in the economy on the energy intensity of gross regional product. The degree of the impact of structural shifts on the dynamics of the energy efficiency of economy of Tatarstan, as well as the dependence of the energy consumption level on the production scale and value added volumes are defined. The research materials may be used in the management of the development of the economy’s real sector, the service sector as at the enterprise level services so in government structures. In addition, the proposed method is suitable for assessing of the level of industrial resource saving, the construction of energy-saving strategies of innovative development, the development of the mechanism of targeted actions for the rational use of resources.